Rapid Enzymatic Method for Pectin Methyl Esters Determination - Lucyna Łękawska-Andrinopoulou; Efstathios G. Vasiliou; Dimitrios G. Georgakopoulos; Constantinos P. Yialouris; Constantinos A. Georgiou (Journal of Analytical Methods in Chemistry)
Pectin is a natural polysaccharide used in food and pharma industries. Pectin degree of methylation is an important parameter having significant influence on pectin applications. A rapid, fully automated, kinetic flow method for determination of pectin methyl esters has been developed. The method is based on a lab-made analyzer using the reverse flow-injection/stopped flow principle. Methanol is released from pectin by pectin methylesterase in the first mixing coil. Enzyme working solution is injected further downstream and it is mixed with pectin/pectin methylesterase stream in the second mixing coil. Methanol is oxidized by alcohol oxidase releasing formaldehyde and hydrogen peroxide. This reaction is coupled to horse radish peroxidase catalyzed reaction, which gives the colored product 4-N-(p-benzoquinoneimine)-antipyrine. Reaction rate is proportional to methanol concentration and it is followed using Ocean Optics USB 2000+ spectrophotometer. The analyzer is fully regulated by a lab written LabVIEW program. The detection limit was 1.47 mM with an analysis rate of 7 samples h−1. A paired t-test with results from manual method showed that the automated method results are equivalent to the manual method at the 95% confidence interval. The developed method is rapid and sustainable and it is the first application of flow analysis in pectin analysis.